Latent effect of passive static stretching on driver clubhead speed, distance, accuracy, and consistent ball contact in young male competitive golfers - Gergley, J. C. (The Journal of Strength and Conditioning Research, 2010)
This investigation was conducted to determine the effect of 2 different warm-up treatments over time on driver clubhead speed, distance, accuracy, and consistent ball contact in young male competitive golfers. Two supervised warm-up treatments, an active dynamic warm-up with golf clubs (AD) and a 20-minute total body passive static stretching routine plus an identical AD warm-up (PSS), were applied before each performance testing session using a counterbalanced design on nonconsecutive days. Immediately after the AD treatment, subjects were instructed to hit 3 full swing golf shots with their driver with 1-minute rest between trials. Immediately after the PSS treatment, subjects were instructed to hit 3 full-swing golf shots with their driver at t0 and thereafter at t15, t30, t45, and t60 minutes with 1-minute rest between swing trials to determine any latent effects of PSS on golf driver performance measures. Results of paired t-tests revealed significant (p < 0.05) decreases in clubhead speed at t0 (-4.92%), t15 (-2.59%), and t30 (-2.19%) but not at t45 (-0.95) or t60 (-0.99). Significant differences were also observed in distance at t0 (-7.26%), t15 (-5.19%), t30 (-5.47%), t45 (-3.30%), and t60 (-3.53%). Accuracy was significantly impaired at t0 (61.99%), t15 (58.78%), t30 (59.46%), and t45 (61.32%) but not at t60 (36.82%). Finally, consistent ball contact was significantly reduced at t0 (-31.29%), t15 (-31.29%), t30 (-23.56%), t45 (-27.49%), and t60 (-15.70%). Plausible explanations for observed performance decrements include a more compliant muscle-tendon unit (MTU) and an altered neurological state because of the PSS treatment. Further, the findings of this study provide evidence supporting the theory that the mechanical properties of the MTU may recover at a faster rate than any associated neurological changes. The results of this inquiry strongly suggest that a total-body passive static stretching routine should be avoided before practice or competition in favor of a gradual AD. Athletes with poor mechanics because of lack of flexibility should perform these exercises after a conditioning session, practice, or competition.